Effects of heterogeneity on the performance of pocket switched networks. Issue 2 (1st June 2014) - Saha, Barun Kumar; Misra, Sudip
Abstract : Pocket switched networks (PSNs), which are formed by mobile devices carried by their users, present an interesting communication paradigm especially in the absence of access to global network connectivity. This work explores the effect of nodes' heterogeneity on the performance of PSNs that use opportunistic communication mechanisms. The focus is on the diversities reflected by the hardware (specifically, buffer size and network interfaces) and software (specifically, routing protocol) of the nodes. Further, the effects of the asymmetric (unidirectional) connections among the devices have also been studied. Although there could be other forms of diversities, for example, different medium access control (MAC) layer protocols, the ones considered here are among the fundamental, and have the potential to render available communication opportunities useless. The work uses time‐varying graphs to represent a PSN with heterogeneous routing protocols and capture its effect. To address the interactions among diverse routing protocols, the use of special nodes, protocol translation units (PTUs), is proposed. Each PTU runs a hybrid routing protocol, which encapsulates the functionality of two or more routing protocols. The results of performance evaluations reflect that deploying PTUs promotes the delivery ratio of the messages by about 15–50%, compared to the levels obtained in, otherwise, homogeneous PSNs.